Examining Sociocultural Influences on Body Image and Self-Acceptance - Yadav, Manisha Khadga (Journal of Development Review, 2025)
When contemplating an individual's physique, perceptions are frequently molded by external evaluations and societal conventions, thereby influencing self-esteem and assessments of appearance. The ideals of thinspiration and fitspiration that are prevalent on social media platforms advocate for weight reduction and fitness objectives, thus impacting perceptions of body image. A positive body image encompasses appreciation and acceptance of one's physical form, shaped by elements such as physical activity and societal expectations. Music videos and lyrics can also affect body image, with objectifying content often detrimentally influencing self-esteem. The societal concept of beauty pageants that celebrate perfection presents difficulties in fostering body positivity. Women, in particular, may experience body dissatisfaction despite having a healthy Body Mass Index. The Bio-Psycho-Social model underscores the interrelationship of biological, psychological, and social factors in body image satisfaction. Although societal pressures and external evaluations can influence perceptions of beauty, embracing one's authentic self and intrinsic value is essential for self-acceptance. This paper highlights music videos promoting a positive body image, significantly impacting women by encouraging them to appreciate their bodies as beautiful. It finds that the pursuit of self-acceptance and an emphasis on inner beauty can yield a more affirmative body image and a stronger sense of self-worth amidst societal criticisms.